ANALYZING THE IMPACT OF REBRANDING IN MECHANICAL INDUSTRY TOWARDS CUSTOMER REACTION: A CASE STUDY IN PT. TURBO TECH INDONESIA. - Nuraini, Haddara (Jurnal Ilmiah Mahasiswa FEB, 2016)
This  minor  thesis  is  purposes  to  examine  the  influence  of  rebranding  towards consumer behavior. There are six independent variables included in the rebranding namely, new brand and service proximity, stronger new and initial brand familiarity, stronger brand image, initial brand attachment, place attachment, and place convenience. The six independent variable were investigated to see the impact on change in service evaluation. The sampling technique used is purposive sampling and the  research  instruments  were  tested  using  the  validity  test,  reliability  test,  and classical assumption test. The hypotheses used partial (T-test) and dominant test. Result of the data analysis from multiple regressions showed that the six variables have a significant effect partially to change in service evaluation. Overall, all independent variables are included in the regression equation to dependent variable which is equal to 50.7 %, while 49.3 % is contributed by other variables that are not included  in  this  equation.  From  the  test  result,  the  dominant  test  shows  that attachment to the service place variable has a dominant influence on change in service evaluation.Keywords: rebranding, customer reaction, service evaluation, proximity between the new brand and the service, brand familiarity, brand image, service place.